155k views
5 votes
Assume x and y are both differentiable functions of t.

Assume x and y are both differentiable functions of t.-example-1

1 Answer

7 votes
First Substitute x=-1 into the equation 4
x^(2) + 3
y^(3) = 28, and you get y=2.

Take the derivative of the equation 4
x^(2) + 3
y^(3) = 28, using implicit differentiation:

8x + 9
y^(2)
(dy)/(dx) = 0

Rearrange this in terms of
(dy)/(dx):


(dy)/(dx) = - (8x)/(9y^(2) )

Keep in mind that
(dy)/(dx) is equal to
( (dy)/(dt) )/( (dx)/(dt) )

Substitute and you will get the following:


( (dy)/(dt) )/( (dx)/(dt) ) = - (8x)/(9y^(2) )

Put in the values for x, y, and
(dy)/(dt) and solve:


( (dy)/(dt) )/( (dx)/(dt) ) = - (8x)/(9y^(2) )


(8)/( (dx)/(dt) ) = (8)/(36)


(dx)/(dt) = 36


User Robotmay
by
6.0k points